2020
DOI: 10.1186/s12903-020-01084-9
|View full text |Cite
|
Sign up to set email alerts
|

Number of natural teeth, denture use and mortality in Chinese elderly: a population-based prospective cohort study

Abstract: Background: The associations between the number of natural teeth/denture use and all-cause mortality remain unclear due to lake of investigation for the potential interaction between tooth loss and denture use and for the potential changes in these exposures over time in older adults. We undertake this study to evaluate the associations of the number of natural teeth and/or denture use with mortality in Chinese elderly. Methods: This is a prospective cohort study of 36,283 older adults (median age: 90). The nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 37 publications
1
28
0
4
Order By: Relevance
“…Furthermore, it was reported that individuals with inadequate masticatory ability, including denture wearers, had a 15% or higher risk of mortality than those with good chewing function 16 , which was similar to that observed in this study. However, in a prospective cohort study, including elderly individuals in China 14 , Yuan et al reported a decrease in mortality (aHR = 0.81; 95% CI: 0.77–0.84) with denture use. The difference may be attributed to the higher number of missing teeth in denture wearers than in non-denture wearers in their study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it was reported that individuals with inadequate masticatory ability, including denture wearers, had a 15% or higher risk of mortality than those with good chewing function 16 , which was similar to that observed in this study. However, in a prospective cohort study, including elderly individuals in China 14 , Yuan et al reported a decrease in mortality (aHR = 0.81; 95% CI: 0.77–0.84) with denture use. The difference may be attributed to the higher number of missing teeth in denture wearers than in non-denture wearers in their study.…”
Section: Discussionmentioning
confidence: 99%
“…As previously reported, individuals with fewer teeth or poor masticatory ability, due to non-replacement of teeth, are at a higher risk of developing cognitive impairment, such as dementia, than those with more than 20 teeth and good masticatory ability 17 , 18 . Numerous studies have reported that masticatory discomfort, caused by tooth loss, is a risk factor for increased mortality 11 , 13 , 14 , 16 . Masticatory discomfort directly influences individual, physical, psychological, and oral health 19 .…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism underlying the association between the presence of < 20 natural teeth and the risk for all-cause mortality is unclear; however, some hypotheses have been suggested. Events such as tooth loss, lead to hypoactivity of the masticatory system and ultimately, insufficient nutrient intake, which can have a negative influence on general health [ 13 , 31 ]. Yoshihara et al reported that participants with < 20 teeth had a significantly lower total protein, animal protein, sodium, vitamin D, vitamin B1, vitamin B6, niacin, and pantothenic acid intake than participants with ≥ 20 teeth [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the multivariate-adjusted model, HR was adjusted for age, sex, smoking habit, alcohol consumption, educational status, hypertension, DM, and perceived mental stress. These adjusted factors for the Cox regression model have also been used in previous studies that surveyed the association between number of teeth and mortality [ 13 15 , 19 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation